STOCK MARKET PERFORMANCE ANALYSIS OF PHARMACEUTICAL, IT AND AUTOMOTIVE COMPANIES FROM POLAND - BĂRNUȚ Cătălin-Florin (Annals of the University of Oradea: Economic Science, 2020)
The pharmaceutical, IT and automotive sectors were chosen for the analysis based on their continuous growth and intense development in the Polish regions during the recent years. Performance represent the key element to stay on the market, therefore, evaluating performance is of high importance for the management, shareholders and trading partners. The study focuses on analyzing the financial statements and the evolution between years 2009 and 2018 of the companies from the mentioned sector listed on the Warsaw Stock Exchange (WSE). Performance was analyzed using the main stock market indicators such as Return on Assets, Return on Equity and Price to Earnings Ratio, considered significant for the study in order to generate conclusions for the decision makers. The study has reached its objectives by providing significant information regarding the performance, evolution and ranking of the analyzed companies, facilitating future investment decisions.